RETORIKA KAMPANYE JOKO WIDODO DALAM PILPRES 9 JULI 2014 (SEBUAH KAJIAN AKSIOLOGI FILSAFAT BAHASA) - Ni Made Rai Wisudariani (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
Political rhetoric tends to have certain political motives and goals. These political goals are under the study of the axiological domain of language philosophy. Related to the phenomenon of democracy in Indonesia, Joko Widodo as one of the president candidates owned a strategy of political rhetoric. The results of the study on the political rhetoric of the speech delivered by Jokowi in Deklarasi Pemilu Berintegritas dan Damai [Declaration of Honest and Peaceful Presidential Election] on June 3, 2014 suggested that from axiological point of view, Jokowi’s speech led to public image creation, formation of general opinion, and persuasive-participant politics.Key words: political rhetoric, axiology